Analysis Of The Concept Of Fulfilling The Political Rights Of Disabled People Reviewed From The Perspective Of Civic Education - Nanggala, Agil; Suryadi, Karim (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2024)
This research aims to analyze the concept of providing political rights for disabled people from a holistic Civics perspective so that it includes the impression of providing political rights that are limited to channelling political votes in elections, and limited to making disabled people political subjects. This research was carried out based on a qualitative approach, using literature study methods, namely data analysis, reduction, display and verification. The results of the research, namely, the concept of containing political rights in a Civics perspective based on a citizenship education approach and citizenship education containing political education, political empowerment, and political involvement of disabled people, so it becomes a political subject, to increase the capacity of civil competence and political literacy of disabled people. The conclusion is that the analysis of the concept that includes the political rights of disabled people from a Civics perspective, not only aims to realize equality for disabled citizens by holistically overcoming stereotyping but also to increase students' civic competence, through philanthropic actions based on civic education for disabled people.